Investigating the Extended Metacommunication Template: How a semiotic tool may encourage reflective ethical practice in the development of machine learning systems - Barbosa, Gabriel Diniz Junqueira; Nunes, José Luiz; De Souza, Clarisse Sieckenius; Barbosa, Simone Diniz Junqueira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
In this paper we present a qualitative study based on speculative design sessions that investigate how developers may use semiotic engineering’s Extended Metacommunication Template (EMT) to engage in reflective ethical practice of software development in a Machine Learning context. The template consists of a series of guiding questions about the development process, split into analysis, design, implementation, and evaluation phases. In the speculative design sessions, participants were presented with design briefs and asked to answer the questions while speculating about their design. Through 8 interviews resulting in 12 hours of recordings, we conducted a thematic analysis looking for salient themes. This process resulted in a codebook with 62 codes, structured around the main entities involved in the machine learning development process: Data, System, Developers, Users, and Stakeholders; as well as 5 themes that aid us in understanding the potential impacts of the template’s use. Our analysis indicates that the EMT shows promise for encouraging reflective ethical practice through linguistic approaches that highlight developers’ agency over the system and its consequences for users and stakeholders. Further study is still necessary into how this tool may be incorporated into real-world software development processes.